2014
DOI: 10.1002/hbm.22464
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal growth and morphology of the hippocampus through childhood: Impact of prematurity and implications for memory and learning

Abstract: The effects of prematurity on hippocampal development through early childhood are largely unknown. The aims of this study were to 1) compare the shape of the very preterm (VPT) hippocampus to that of full-term (FT) children at 7 years of age, and determine if hippocampal shape is associated with memory and learning impairment in VPT children, 2) compare change in shape and volume of the hippocampi from term-equivalent to 7 years of age between VPT and FT children, and determine if development of the hippocampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 57 publications
1
53
1
1
Order By: Relevance
“…Smaller bilateral hippocampal volume in VPT samples compared with controls has been described at school‐age (~9% volume reduction),12, 13 adolescence (~14% volume reduction),14, 15 and adulthood16, 17 although some studies have found no hippocampal volume differences when correcting for factors such as intracranial volume 18, 19. Interestingly, hippocampal volume at term, but not at 7 years of age (or the amount of growth between these time‐points), has been associated with episodic memory abilities at age seven 12, 18, 20. This suggests that children with early hippocampal damage may have a limited capacity for the development of episodic memory functions.…”
Section: Episodic Memorymentioning
confidence: 96%
“…Smaller bilateral hippocampal volume in VPT samples compared with controls has been described at school‐age (~9% volume reduction),12, 13 adolescence (~14% volume reduction),14, 15 and adulthood16, 17 although some studies have found no hippocampal volume differences when correcting for factors such as intracranial volume 18, 19. Interestingly, hippocampal volume at term, but not at 7 years of age (or the amount of growth between these time‐points), has been associated with episodic memory abilities at age seven 12, 18, 20. This suggests that children with early hippocampal damage may have a limited capacity for the development of episodic memory functions.…”
Section: Episodic Memorymentioning
confidence: 96%
“…While limited evidence is available to date, it is possible that certain dysmorphic features of important structures such as the hippocampus, cerebellum, and corpus callosum may assist is predicting future maturation processes and later neurodevelopmental impairments. 48,51 Furthermore, directly related to tissue and regional volumes is cortical folding. Primary sulci form from 14 to 26 weeks GA, secondary sulci evolve between 30 and 35 weeks, and tertiary sulci from 36 weeks, and as such, a critical period for cortical gyration for VP infants occurs when they are critically ill and exposed to a range of potentially harmful agents and procedures.…”
Section: Volumetric Mrimentioning
confidence: 99%
“…The susceptibility of these regions to methylation changes was also seen in models of maternal separation and in prenatal alcohol exposure. The number of genes associated to each pathway is in parenthesis infants had impaired hippocampal and cortical growth seen 7 years later 69,70 and even signs of increasing atrophy over time. [63][64][65][66] One major group of pathways that emerged from our methylome analysis following neonatal inflammation-induced WMI was related to the axon.…”
Section: F I G U R E 4 Methylation Levels Of Genes Of Interest Associmentioning
confidence: 99%